Promoter hypermethylation and loss of CD133 gene expression in colorectal cancers - Jeon, You-Kyung (The WJG Press and Baishideng, 2010)
AIM: To understand CD133 promoter hypermethylation and expression in 32 colorectal cancer cell lines. METHODS: Nucleic acid was isolated from 32 colorectal cancer cell lines and CD133 expression levels were measured by reverse transcription-polymerase chain reaction (RT-PCR) and real-time PCR. Promoter methylation status of the CD133 gene was analyzed with a methylation-specific PCR after sodium-bisulfite modification and by clonal sequencing analysis. The correlation between expression and promoter methylation of CD133 gene was confirmed with treatment of 5-aza-2’-deoxycytidine. RESULTS: We measured CD133 expression levels in 32 colorectal cancer cell lines. RT-PCR analysis showed undetectable or low levels of CD133 expression in 34.4% of cell lines. To verify the relation between CD133 expression and methylation status of the CD133 gene promoter in colorectal carcinogenesis, CD133 gene promoter hypermethylation was analyzed in 32 cancer cell lines. Promoter hypermethylation was detected in 13 (40.6%) of the cell lines using methylation specific-PCR and confirmed by bisulfite sequencing analysis. Treatment of 11 of the cell lines with the demethylation agent 5-aza-2’-deoxycytidine recovered CD133 expression in most of them. CONCLUSION: Transcriptional repression of CD133 is caused by promoter hypermethylation of the CD133 CpG islands in some of colorectal cancer cell lines. The study may contribute to the understanding of the role of CD133 inactivation in the progression of colorectal cancers.